Efektivitas Adsorben Berbasis Alginat Dan Karbon Aktif Ampas Kopi Dalam Menurunkan Kadar Cod Limbah Cair Industri Tahu - Aisyah, Siti Nur; Daulay, Abdul Halim; Ong, Russell (Fakultas Teknik UMSU, 2025)
Oxygen Demand (COD), requiring treatment before disposal into the environment. This study aims to evaluate the effectiveness of an adsorbent based on coffee waste-derived activated carbon and sodium alginate in reducing COD levels in tofu wastewater. The activated carbon used has been tested for quality and meets the Indonesian National Standard (SNI 06-3730-1995). The remediation process was conducted using five different adsorbent composition variations. The results showed that the combination of coffee waste-derived activated carbon and sodium alginate significantly reduced COD levels, achieving a maximum reduction efficiency of 90.55% at the optimum variation (Sample E). The adsorption mechanism involving alginate polymers and the porosity of activated carbon contributed to the effective removal of organic compounds from the wastewater. Based on the analysis, this method has proven to be effective in reducing COD levels, making it a potential environmentally friendly alternative for treating tofu industry wastewater.